Engaging the millennial generation student with e-learning in dentistry / Siti Mariam Ab Ghani ... [et al.] - Lim, Tong Wah; Mustaza, Teh Adilla; Abu Hassan, Mohamed Ibrahim (Penerbit UiTM (UiTM Press), 2016)
The need to move from traditional teaching and learning methods to more interactive approaches has been in high demand from the young generation of tech-savvy students. However, this move in dentistry has been very slow in Malaysia, despite the exponential growth of e-learning in other disciplines. Nevertheless, the Centre for Restorative Dentistry Studies (UiTM) is in the transformation to actively embrace the e-learning curriculum structures combined with traditional teaching methods. Three peer-reviewed e-modules were developed with each module comprised audio-visual lectures, video demonstrations and online students' assessments. The concept of flipped classroom were applied where these e-modules were uploaded to i-Learn (the university online learning portal) for students to assess at home. Questionnaires were given to assess their perception towards e-modules received. Conventional lectures (82.4%), e-modules (64.7%) and textbooks (64.7%) were reported as the most often material used by students. After the exposure to e-modules, 15 students (29.4%) suggested replacing lectures with e-modules but 36 students (70.6%) insist on having the conventional lectures combined together. Major drawbacks and students concerns (58.8%) were technical problems and the lack of direct communications with the lecturers. However, all students (100%) stated that they would continue to use the e-modules in the future and request for more in other topics. It was evidently found that the students 'perceptions to e-modules are generally positive. However, the drawbacks and their main concerns are points to be considered before further development of a comprehensive blended learning curriculum in the Faculty.